Lipid Profile Changes Among Male and Female Regarding their Body Mass Index and Diet a Comparative Cross-Sectional Study - Muhammad Naveed Najeeb, Zunaira Kanwal, Nazish Mehmood Aisha, Umaira Munir, Syed Saim Ali Shah, Hina Malik, Naveed Shuja, Arslan Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Place and Duration: Present study was conducted in medical units of Jinnah hospital Lahore, Services hospital Lahore and Bahawal Victoria hospital Bahawalpur from February 2022 to November 2022. Results: The findings of present study indicated different levels of cholesterol, triglycerides, low density lipoproteins and high density lipoproteins with comparative significant (P≤0.05) changes in different groups as compared with control Group-A. A remarkable changes in cholesterol, triglycerides, LDL, HDL levels in Group-B and Group-C were seen (160.1±0.02, 112.1±0.01, 106.1±0.01, 40.1±0.01) (210.2±0.01, 152.1±0.02, 120.2±0.03, 37.4±0.01) respectively. While in Group-E as compared with Group-D the cholesterol, triglycerides, LDL, HDL levels (230.2±0.04, 192.1±0.02, 130.1±0.01, 42.1±0.02) (170.2±0.04, 112.1±0.02, 110.2±0.03, 50.4±0.01) were high as compared with the individuals of Group-D. Practical implication: The regular health awareness programs were not available for local population from health administration while lipid profile is directly proportional to the cardiac medical complications in all over the world. The main task of present study was to provide exact medical awareness to the people about diet related variations of cholesterol, triglycerides, LDL and HDL levels and ultimately it was concluded that dyslipidemia can occur in those with a normal BMI as well as those who are obese or overweight.